Investigating the Effect of Inquiring Mind Want to Know Assissted by Audiovisual Media and Learning Motivation Students’ Writing Skills - Nofya, Mona; Atmazaki, Atmazaki (Journal of Languages and Language Teaching, 2024)
This study aimed to describe the effect of using the inquiring mind want to know technique assisted by audiovisual media in the learning outcomes of observation report text writing skills of class X students of SMA Negeri 1 Painan. This study was quantitative research that applied the experimental method with a 2×2 factorial design. Data collection was carried out by tests and questionnaires, tests were carried out to obtain data on the results of learning the skills of writing text reports on observations and questionnaires were carried out to obtain data on learning motivation. The data analysis process was carried out using the IMB SPSS Statistics 26 application. Based on the result of data analysis in this study, several conclusions were obtained. First, there was an influence of the use of the inquiring mind want to know technique assisted by audiovisual media on the learning outcomes of the writing skills of observation reports. Second, there is an effect of using the inquiring mind want to know technique assisted by audiovisual media on the learning outcomes of students' observational report writing skills with high learning motivation. Third, there is an effect of using the inquiring mind want to know technique assisted by audiovisual media on the learning outcomes of students' observational report writing skills with low learning motivation. Fourth, there is no interaction between the inquiring mind want to know technique assisted by audiovisual media and learning motivation in influencing the writing skills of observation report texts.